When do examinees change their initial answers? The influence of task instruction, response confidence, and subjective task difficulty. (December 2022) - Tiffin-Richards, Simon P.; Lenhart, Jan; Marx, Peter
Abstract: Changing a small number of answers to multiple-choice questions reliably improves test-scores, although it remains unclear how examinees select which initial answers to change and whether answer-changing behaviour is susceptible to instruction. We tested the effect of an instructional intervention on the number of changes made by examinees on a mock-exam in a controlled experimental design. We also examined how examinees' confidence with their initial answers, and their judgement of how difficult each exam question was, predicted their answer-changing behaviour. We found that the number of changes made increased, to a small extent, through instruction, without increasing the rate of errors. The likelihood of changing an initial answer decreased with examinees' feeling of confidence, and increased with their feeling of difficulty. This is consistent with the theory that examinees use metacognitive experiences to select which initial answers to change on exams. Highlights: Changing initial answers on exams typically improves test performance. The number of answers changed was increased by an instruction intervention. Feeling of confidence was negatively associated with answer-changing likelihood. Feeling of difficulty was positively associated with answer-changing likelihood.